Contribution to the identification of Dianthus rupicola (Caryophyllaceae) subspecies using morphological and molecular approaches - Domina, Gianniantonio; Scibetta, Silvia; Scafidi, Filippo; Giovino, Antonio (Phytotaxa, 2017)
The systematic relationships between the five different subspecies actually recognized within Dianthus rupicola (subsp. aeolicus, subsp. bocchorianus, subsp. hermaensis, subsp. lopadusanus and subsp. rupicola), were assessed by means of morphometric and molecular analysis. Our results highlighted the molecular differences between the five subspecies of D. rupicola and a morphological differentiation of four groups being D. rupicola subsp. aeolicus and D. rupicola subsp. rupicola partly overlapping. At the present state of knowledge, a subspecific status seems the most appropriate for all the recognized subspecies of D. rupicola. The names D. aeolicus, D. bisignanii var. virescens, D. hermaeensis, D. rupicola are here lectotypified respectively on specimens preserved at PAL, NAP, P, and BOLO, while D. bisignanii s.str. is lectotypified on a Tenore’s image and a epitype (at K) is designated. Concerning the name D. rupicola subsp. bocchorianus the holotype is traced.